Aerosol Properties Observed in the Subtropical North Pacific Boundary Layer. Issue 18 (24th September 2017) - Royalty, T. M.; Phillips, B. N.; Dawson, K. W.; Reed, R.; Meskhidze, N.; Petters, M. D.
Abstract: The impact of anthropogenic aerosol on climate forcing remains uncertain largely due to inadequate representation of natural aerosols in climate models. The marine boundary layer (MBL) might serve as a model location to study natural aerosol processes. Yet source and sink mechanisms controlling the MBL aerosol number, size distribution, chemical composition, and hygroscopic properties remain poorly constrained. Here aerosol size distribution and water uptake measurements were made aboard the R/V Hi'ialakai from 27 June to 3 July 2016 in the subtropical North Pacific Ocean. Size distributions were predominantly bimodal with an average integrated number concentration of 197 ± 98 cm −3 . Hygroscopic growth factors were measured using the tandem differential mobility analyzer technique for dry 48, 96, and 144 nm particles. Mode kappa values for these were 0.57 ± 0.12, 0.51 ± 0.09, and 0.52 ± 0.08, respectively. To better understand remote MBL aerosol sources, a new algorithm was developed which decomposes hygroscopicity distributions into three classes: carbon‐containing particles, sulfate‐like particles, and sodium‐containing particles. Results from this algorithm showed low and steady sodium‐containing particle concentrations while the sulfate‐like and carbon‐containing particle concentrations varied during the cruise. According to the classification scheme, carbon‐containing particles contributed at least 3–7%, sulfate‐like particles contributed at most 77–88% and sodium‐containing particles at least contributed 9–16% to the total aerosol number concentration. Size distribution and hygroscopicity data, in conjunction with air mass back trajectory analysis, suggested that the aerosol budget in the subtropical North Pacific MBL may be controlled by aerosol entrainment from the free troposphere. Key Points: Aerosol water uptake data over the ocean can be used to estimate the number concentration of sodium‐containing particles The contribution of 50 to 150 nm diameter sodium‐containing particles to the aerosol budget over the North Pacific Ocean was at least ~9–16% Size distributions and water uptake properties of the marine boundary layer aerosol were influenced by free tropospheric sources